Cerebral Metabolism Related to Cognitive Impairments in Multiple System Atrophy - Shen, Cong; Chen, Li; Ge, Jing-Jie; Lu, Jia-Ying; Chen, Qi-Si; He, Shu-Jin; Li, Xin-Yi; Zhao, Jue; Sun, Yi-Min; Wu, Ping; Wu, Jian-Jun; Liu, Feng-Tao; et al. (Frontiers in Neurology, 2021)
Objective: We aimed to characterize the cognitive profiles in multiple system atrophy (MSA) and explore the cerebral metabolism related to the cognitive decline in MSA using 18F-fluorodeoxyglucose (18F-FDG) Positron Emission Tomography (PET). Methods: In this study, 105 MSA patients were included for cognitive assessment and 84 of them were enrolled for 18F-FDG PET analysis. The comprehensive neuropsychological tests covered five main domains including execution, attention, memory, language and visuospatial function. The cognition statuses were classified to MSA with normal cognition (MSA-NC) and MSA with cognitive impairment (MSA-CI), including dementia (MSA-D) and mild cognitive impairment (MSA-MCI). With 18F-FDG PET imaging, the cerebral metabolism differences among different cognitive statuses were analyzed using statistical parametric mapping and post hoc analysis. Results: Among 84 MSA patients, fifty-two patients were found with MSA-CI, including 36 patients as MSA-MCI and 16 patients as MSA-D. In detail, the cognitive impairments were observed in all the five domains, primarily in attention, executive function and memory. In 18F-FDG PET imaging, MSA-D and MSA-MCI patients exhibited hypometabolism in left middle and superior frontal lobe compared with MSA-NC (p<0.001). The normalized regional cerebral metabolic rate of glucose (rCMRglc) in left middle frontal lobe showed relative accuracy in discriminating MSA-CI and MSA-NC (areas under the curve (AUC)= 0.750; 95% CI, 0.6391-0.8609). Conclusions: Cognitive impairments were not rare in MSA, and the hypometabolism in frontal lobe may contribute to such impairments.